STUDI PERBANDINGAN PEMBELAJARAN HADIS UNIVERSITAS ISLAM MADINAH DAN UNIVERSITAS ISLAM NEGERI SUNAN AMPEL SURABAYA - Muhid, Muhid (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
The study of hadith in Indonesia has entered a new phase, marked by domestic universities starting to make hadith an independent study program. In an effort to improve the quality of hadith studies, which are relatively new, comparative study discourse is needed with established hadith studies. This article tries to explore the characteristics of hadith studies at the Islamic University of Madinah and Sunan Ampel State Islamic University, Surabaya with the aim of finding out the uniqueness of learning from each university. This research uses a qualitative approach, in an effort to extract data, interviews were conducted with academics from the hadith science study program, Sunan Ampel State Islamic University, Surabaya and hadith science graduates from the Islamic University of Madinah, then a comparative method was used to analyze the characteristics of hadith studies at the two universities. The results of the research reveal that the curriculum of the two universities is not much different, the Madinah Islamic University is more dominant in the hadith memorization system, while the Sunan Ampel Surabaya State Islamic University strengthens understanding of methodology and reasoning. It is hoped that this article can bring changes for the better in the study of hadith in Indonesia.